Characterization of Extreme Acidophile Bacteria (Acidithiobacillus ferrooxidans) Bioleaching Copper from Flexible PCB by ICP-AES - Gu, Weihua; Bai, Jianfeng; Dai, Jue; Zhang, Chenglong; Yuan, Wenyi; Wang, Jingwei; Wang, Pengcheng; Zhao, Xin (Journal of Spectroscopy, 2014)
In order to improve copper leaching efficiency from the flexible printed circuit board (PCB) by Acidithiobacillus ferrooxidans, it is necessary to quantitatively measure the bacteria bioleaching copper under extreme acidic condition from flexible PCB. The inductively coupled plasma-atomic emission spectroscopy (ICP-AES) is a very accurate way to analyze metals in solution; this paper investigated the optimal conditions for copper bioleaching by Acidithiobacillus ferrooxidans from flexible PCB through ICP-AES. The conditions included particle size of flexible PCB powder, quantity of flexible PCB powder, initial pH of culture medium, bacteria inoculation, bacteria activation time, and quantity of FeSO4·7H2O. Prior to ICP-AES measurement, culture solution was digested by aqua regia. The experimental results demonstrated that flexible PCB contained one main metal (copper); this was associated with the structure of flexible PCB. The optimization conditions were in 50 mL medium, flexible PCB 10 g/L, particle size of flexible PCB 0.42~0.84 mm, culture medium initial pH 2.5, bacteria inoculation 5%, bacteria activation time 5 d, and quantity of FeSO4·7H2O 30 g/L. Under the optimization condition, the leaching rate of copper was 90.10%, which was 42.4% higher than the blank group. For the ICP-AES determination, it reached a conclusion that the best corresponding wavelength (nm) of copper will be 224.7 (nm).